Global research trends and prospects related to tumor microenvironment within Triple Negative Breast Cancer: a bibliometric analysis - Li, Peiting; Li, Jun; Tong, Xiaofei; Xiao, Zhenyang; Diao, Wuliang; Zhong, Chi; Zhou, Jianda; Wu, Wei (Frontiers in Immunology, 2023)
Background and aims: The tumor microenvironment (TME) has pivotal parts within multiple tumor models of onset / progression, such as triple-negative breast cancer (TNBC). This bibliometric analysis was developed to explore trends and research niches revolving around TME in TNBC.Methods: Web of Science Core Collection was queried for identifying studies linked with TME in TNBC, after which the VOSviewer, CiteSpace, and R software programs were used to conduct bibliometric analyses and to generate corresponding visualizations.Results: In total, this study included 1,604 studies published from 2005-2023. The USA and China exhibited the highest numbers of citations, and the research institutions with the greatest output in this field included Harvard University,